2022
DOI: 10.7150/ijbs.68873
|View full text |Cite
|
Sign up to set email alerts
|

Atractylenolide III ameliorates Non-Alcoholic Fatty Liver Disease by activating Hepatic Adiponectin Receptor 1-Mediated AMPK Pathway

Abstract: Background: Nonalcoholic fatty liver disease (NAFLD) is the most frequent cause of chronic liver diseases worldwide. At present, there are no effective pharmacological therapies for NAFLD except lifestyle intervention-mediated weight loss. Atractylenolide III (ATL III), the major bioactive component found in Atractylode smacrocephala Koidz, has been shown to exert anti-oxidant, anti-tumor, anti-allergic response, anti-bacterial effects and cognitive protection. Here we investigate the therapeutic potential and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 49 publications
2
27
1
Order By: Relevance
“…Treatment with L. plantarum ZJUIDS14 induced a marked decrease in OGTT and ITT AUC values. Consistent with other studies (27)(28)(29), HFD significantly increased the levels of plasma TG, FFA, TC, and LDL-C. Moreover, the plasma levels of HDL-C were increased and TG, FFA, and LDL-C were distinctly reduced * P < 0.05, * * P < 0.01, * * * P < 0.001 vs NFD group; # P < 0.05, ## P < 0.01 vs HFD group.…”
Section: Discussionsupporting
confidence: 93%
“…Treatment with L. plantarum ZJUIDS14 induced a marked decrease in OGTT and ITT AUC values. Consistent with other studies (27)(28)(29), HFD significantly increased the levels of plasma TG, FFA, TC, and LDL-C. Moreover, the plasma levels of HDL-C were increased and TG, FFA, and LDL-C were distinctly reduced * P < 0.05, * * P < 0.01, * * * P < 0.001 vs NFD group; # P < 0.05, ## P < 0.01 vs HFD group.…”
Section: Discussionsupporting
confidence: 93%
“…Besides, it can inhibit the secretion of gluconeogenesis-related enzymes and glucagon-like peptide 1 (GLP-1) as well as glucagon signaling by delaying the absorption of glucose in the gastrointestinal tract ( Sunny et al, 2017 ). In an in vivo and in vitro experiment, Li et al (2022) found, by combining computer-aided design analysis, that Atractylenolide III could reduce lipid accumulation by upregulating liver adiponectin receptor 1, activating AMPK pathway, improving the phosphorylation of LKB1 and AMPK, and promoting the expression of fatty acid oxidation proteins CPT1A and PGC1α; At the same time, it could upregulate the activities of antioxidant proteins Sirt3 and Nrf2, inhibit oxidative stress response, and ultimately improve NAFLD ( Li et al, 2022 ). In the in vitro experiment of hepatocytes exposed to ethanol, dihydroquercetin was found to significantly increase the activity and phosphorylation of LKB1 and AMPK to inhibit the expression of ACC and SREBP-1c, thereby inhibiting lipid production, promoting fatty acid oxidation and finally reducing fat accumulation ( Zhang et al, 2018 ).…”
Section: Research Status Of Fatty Liver Disease Treatment Drugsmentioning
confidence: 99%
“…Atractylenolide III is the major bioactive component found in Atractylodes macrocephala Koidz. The study showed that Atractylenolide III ameliorated liver injury and liver lipid accumulation in HFD-induced NAFLD mouse models by activating the AMPK/SIRT1 pathway [ 119 ]. Salvianolic acid A is a natural polyphenol compound extracted from Salvia miltiorrhiza Bunge (known as Danshen in China).…”
Section: Potential Natural Ingredients For the Treatment Of Nafldmentioning
confidence: 99%
“…Antrodan High-fat diet (HFD)-fed mouse [49] (2) Emodin Egg yolk powder-fed Zebrafish [88] (3) Four flavonoids extracted from Lomatogonium rotatum High fructose-fed rats [89] (4) Oxyresveratrol HFD-fed mouse, liver X receptor α (LXRα) stimulated HepG2, Hep3B and Huh-7 cells [90] (5) Cynandione A LXRα stimulated HepG2 cells [91] (6) Gomisin N HFD-fed mouse, LXRα or palmitic acid (PA) stimulated HepG2 cells [92] (7) Tomatidine HFD-fed mouse, Oleic acid (OA) stimulated FL83B [93] (8) Licochalcone A HFD-fed mouse, OA stimulated HepG2 cells [94] Alleviating oxidative stress (9) Hesperetin HFD-fed rat, OA stimulated HepG2 cells [99] (10) Gastrodin HFD-fed mouse, high-fat and high-carbohydrate diet (HFHC)-fed rat, OA stimulated HL-7702 cells [ Alleviating endoplasmic reticulum stress (16) Aucubin HFD-fed rat, PA stimulated HepG2 cells [112] (17) Geniposide HFD-fed rat, PA stimulated HepG2 cells [112] (18) Tanshinone IIA PA stimulated HepG2 cells [114] Alleviating inflammatory reaction (19) Resveratrol HFD-fed mouse [116] (20) Atractylenolide III HFD-fed mouse, OA plus PA stimulated HepG2 cells [119] (21) Salvianolic acid A HFHC-fed mouse, PA stimulated HepG2 cells [120] (22) Silibinin MCD-fed mouse, OA plus PA stimulated mouse NCTC-1469 cells [121] (23) Honokiol MCD-fed mouse, OA plus PA stimulated mouse NCTC-1469 cells [122] (24) Ursolic acid HFD-fed mouse [123] (25) Hairy calycosin HFD-fed rat [124] Silibinin is a flavonolignan isolated from the fruit and seeds of Milk thistle (Silybum marianum (L.) Gaertn.). Silibinin prevents NASH by modulating the JNK pathway.…”
Section: Regulating Lipid Metabolism (1)mentioning
confidence: 99%